KESIAPAN PENERAPAN REGISTER IMUNISASI ELEKTRONIK NASIONAL DI PROVINSI BANTEN DAN MALUKU UTARA - Rahmadewi, Pama; Heryawan, Lukman; Lazuardi, Lutfan (Jurnal Kesehatan Masyarakat, 2023)
Immunization programs have proven to be effective and efficient in providing health services, but in practice, many challenges are still encountered, among them those related to achieving immunization targets and improving immunization services. The COVID-19 pandemic has transformed Indonesia's national health system by digitizing health data. In the immunization program, in 2022, the Ministry of Health of the Republic of Indonesia launched the SehatIndonesiaKu (ASIK) application as a national Electronic Immunization Register (EIR). Readiness assessment needs to be carried out on the application of national RIE so that it is optimal. This study aims to explore readiness for implementing national EIR in Banten and North Maluku Provinces. This is a descriptive study using a qualitative design with the Rapid Assessment Procedures (RAP) method. Research informants are immunization program managers in Banten and North Maluku Provinces. The instruments used for data collection were screening questionnaires, FGD guidelines, interview questionnaires, and observation sheets. Information about the readiness to implement national RIE was obtained through focus group discussions (FGD) and interview discussions during site visits. The data was then analyzed qualitatively. The content analysis process used to determine codes, categories, and themes in this study uses OpenCode 4.02 software. The readiness to implement national EIR in terms of organizational culture can be seen from the acceptance of ASIK as a national EIR and the adoption strategies chosen in the two provinces. In the aspect of management and leadership, maintenance of the quality of immunization data has been carried out through monitoring, confirmation, validation, and evaluation. The readiness of the operational aspect can be seen from the implementation of ASIK, which began with national piloting for the implementation of BIAN 2022, followed by ASIK piloting for routine immunization in several selected provinces, one of which is in North Maluku Province. On the technical aspect, there are application innovations related to immunization in the regions, indicating that the regions are quite experienced with immunization information systems. The readiness for implementing national EIR is quite potential, but it needs more support from regional heads, regulations, SOPs, and workflow as a reference for implementing national EIR, improvements to national EIR applications, and other constraints outside the system, as well as increasing digital skills for immunization managers to overcome problems and maintain system continuity. A national RIE implementation strategy is recommended to support the program's success.